Assessment of Antidepressant Activity of Ethanolic Extract of Hibiscus rosa sinensis Linn. Petals in Comparison with Fluoxetine and its Toxicity in Swiss Albino Mice: A Preclinical Research Protocol - Sneha Ray; Swanand S Pathak (Journal of Clinical and Diagnostic Research)
Introduction: Depression is the most common mental health condition today, with about 5% of adults worldwide thought to be affected. Hibiscus rosa sinensis (HRS) Linn (Malvaceae) blooms are a rich source of flavonoids, which have been shown to possess antidepressant properties. The current investigation seeks to evaluate the antidepressant effects of flavonoids in HRS Linn petals. Need of the study: Strong allopathic drugs such as monoamine oxidase inhibitors, Selective Serotonin Reuptake Inhibitors (SSRIs) and tricyclic antidepressants increase the levels of these neurotransmitters. However, there are disadvantages associated with these medications. Since there are not many research studies on antidepressants derived from plants, this topic requires assessment. This approach offers a gradual and effective healing process, utilising harmless herbs and derived formulations that are also cost-effective and reliable. Aim: To compare the safety and effectiveness of ethanolic extracts of HRS Linn petals to fluoxetine (an SSRI) in male Swiss albino mice. Materials and Methods: An experimental study will be conducted at the Animal House, Datta Meghe Institute of Higher Education and Research (DMIHER), Sawangi, Wardha, Maharashtra, India from August 2024 to February 2025. The study procedure will involve procuring standard drugs, screening animals, preparing a solution for the test drugs and determining the LD50. The antidepressant effects of crude ethanol extract from the floral parts of HRS will be compared to standard fluoxetine treatment using four different behavioural tests: the Elevated Plus Maze (EPM), tail suspension, forced swim and Open Field Tests (OFT). The extract will be administered at doses of 100 mg/kg, 250 mg/kg and 500 mg/kg, while fluoxetine will be given at a dose of 15 mg/kg. The acute toxicity of the HRS extract will also be assessed using four different doses: 5 mL/kg, 50 mg/kg, 300 mg/kg and 2000 mg/kg. The toxicity test will be evaluated based on Organisation for Economic Co-operation and Development (OECD) 423 guidelines. An Analysis of Variance (ANOVA) test will be applied for intergroup comparison of differences in behavioural tests and acute toxicity among these four groups. A p-value <0.05 will be considered significant.